SPE Latin American and Caribbean Petroleum Engineering Conference 2003
DOI: 10.2118/81082-ms
|View full text |Cite
|
Sign up to set email alerts
|

Application of Aphrons Technology in Drilling Depleted Mature Fields

Abstract: Depleted zones are intrinsic to most mature reservoirs throughout the world. The associated issues of effective, safe and economically viable well construction, completion and workover within low pressure environments become more challenging on a daily basis. This paper discusses the application of aphron drilling fluid technology, which offers a unique alternative option that can significantly improve the operational and economic aspects for continued development of these marginal assets. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…(1)The adversary aspects, including unsatisfactory deep drill hole debris disposal, the rough drill hole wall at the soft and loose coal seam, difficulties in debris disposal, and other limitations existing in the downward drilling technology of coal mines, were all considered in this experimental study. In addition, debris disposal technology was optimized to ensure that the effective drilling depth could conform to technical requirements, thereby improving the effective utilization rate of drill holes (2)The magnet powder commonly used in beneficiation and mineral processing was selected as the suspension for debris disposal in the drill hole. This selection was based on the fundamental properties of the drilling debris in the drill hole of the coal mine as well as the characteristics of the existing suspending agents combined…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1)The adversary aspects, including unsatisfactory deep drill hole debris disposal, the rough drill hole wall at the soft and loose coal seam, difficulties in debris disposal, and other limitations existing in the downward drilling technology of coal mines, were all considered in this experimental study. In addition, debris disposal technology was optimized to ensure that the effective drilling depth could conform to technical requirements, thereby improving the effective utilization rate of drill holes (2)The magnet powder commonly used in beneficiation and mineral processing was selected as the suspension for debris disposal in the drill hole. This selection was based on the fundamental properties of the drilling debris in the drill hole of the coal mine as well as the characteristics of the existing suspending agents combined…”
Section: Discussionmentioning
confidence: 99%
“…The problem is that the borehole could produce more drilling debris during gas extraction when the stress is con-centrated on the coal seam, thereby resulting in low gas extraction efficiency. Failed disposal of residual drilling debris in the drill hole will not only make it challenging to utilize the borehole completely but also hinder gas migration and block holes of the casing pipe, which will become serious under ponding conditions [1][2][3][4]. In addition, residual drilling debris in the drill hole will result in nonuniform negative pressure of extraction, reducing the radial scope of gas extraction to a certain degree, aggravating the formation of hole collapse, and degrading the gas extraction effect.…”
Section: Introductionmentioning
confidence: 99%
“…Ehsan et al [12] investigate the rheological characteristics of aphron-based drilling fluids and reported that the rheology of such fluids can be more accurately described by Herschel-Bulkley fluid model. Some investigations in this direction revealed that aphron drilling fluids can be efficiently utilized in oil fields for drilling in the depleted formation with a very small loss of drilling fluids due to the presence of stabilized aphron [8,14,25] The application of aphron drilling fluid in reducing the formation damages during the drilling of horizontal wells is reported in [9].…”
Section: Introductionmentioning
confidence: 99%
“…CGAs have been frequently used as drilling fluid for depleted fractured formations. Their ability to survive longer at higher pressures in comparison to regular foams as well as easy production and easy handling have made them a suitable choice for drilling engineering [3][4][5][6][7][8][9][10][11]. From the review article [10], it can be seen that many papers have studied the effect of different parameters, including stirring time and speed, surfactant and polymer type, and concentration, etc., on the formation, stability, and performance of CGAs.…”
Section: Introductionmentioning
confidence: 99%